High transparent polyester film and production method of the same

JP2025023455APending Publication Date: 2025-02-17TORAY INDUSTRIES INC

Patent Information

Application Number
JP2023127579
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-17

Smart Images

  • Figure 2025023455000001
    Figure 2025023455000001
  • Figure 2025023455000002
    Figure 2025023455000002
  • Figure 2025023455000003
    Figure 2025023455000003
Patent Text Reader

Abstract

To provide a high transparent polyester film which hardly generates foreign matters such as a gelled substance even when being re-melted, has heat resistance, and can maintain extremely high quality even when recycling is performed, and a method for producing the same.SOLUTION: A polyester film has a base material layer containing a polyester resin as a main component, has an internal haze of 0.5% or less, and satisfies all the following expressions (I) to (IV). Expression (I): 5 ppm≤germanium element content (mass basis)≤80 ppm, Expression (II): 5 ppm≤manganese element content (mass basis)≤40 ppm, Expression (III): 4 ppm≤sodium element content (mass basis)≤40 ppm, and Expression (IV): 14 ppm≤metal element content (mass basis)≤100 ppm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a highly transparent polyester film and a manufacturing method using recycled materials. [Background technology]

[0002] Polyester films have excellent mechanical properties, thermal properties, chemical resistance, electrical properties, and moldability, and are used in a variety of applications. Among polyester films, polyethylene terephthalate (hereinafter sometimes referred to as PET) films in particular have excellent transparency and processability, and are therefore ideally used as highly transparent optical films, particularly for displays and touch panels.

[0003] Generally, polyester resins, and PET in particular, are produced by producing an esterification product from a dicarboxylic acid such as terephthalic acid or an ester-forming derivative thereof and ethylene glycol or a glycol mainly composed of ethylene glycol, and then polycondensing the esterification product at high temperature and high vacuum in the presence of a polycondensation catalyst.

[0004] Germanium compounds, titanium compounds, antimony compounds, etc. have been used as polycondensation catalysts for producing polyester resins, but antimony compounds, which are inexpensive and have excellent catalytic activity, are the most widely used. However, when antimony compounds are used as polycondensation catalysts, they tend to precipitate as insoluble metal particles during the production stage of polyester resins. Therefore, there are problems such as defects occurring when the obtained polyester resin is molded into a film, and the antimony compounds inducing minute gels during melt extrusion.

[0005] In recent years, the quality requirements for highly transparent films, mainly for optical applications, have been increasing, and technology that suppresses the above-mentioned defects while maintaining mechanical and thermal properties is desired. Furthermore, due to the increasing demand for reducing the environmental impact, it has become necessary to utilize recycled materials regenerated from the film itself in order to reduce energy consumption and CO2 emissions. For example, there is a growing expectation for films that have recycling durability that can maintain high quality by suppressing the generation of foreign matter, especially minute gelled matter, and the decrease in polyester viscosity even after repeated use.

[0006] In response to these problems, the following studies have been carried out. For example, Patent Document 1 discloses a technique for suppressing the generation of metallic antimony by reducing the amount of antimony compound added. Patent Document 2 discloses a method for producing polyester using a specific amount of manganese compound, an alkali metal compound, a phosphorus compound, and an organotitanium compound to suppress the generation of insoluble foreign matter in the polymer. Patent Document 3 discloses a technique for improving the transparency and crystallinity of polyester using a magnesium compound and a phosphorus compound as a catalyst with a germanium compound. In addition, Patent Document 4 proposes a system for peeling and cleaning a functional layer provided on a film and using it as a recycled raw material from the viewpoint of recyclability. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 3-146707 [Patent Document 2] Japanese Patent Application Publication No. 63-278927 [Patent Document 3] JP 2003-137992 A [Patent Document 4] JP 2021-160351 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, in the method described in Patent Document 1, although it is possible to suppress the generation of metallic antimony to a certain extent, it is impossible to reduce it to a level required for a film that requires high transparency and quality. In the method described in Patent Document 2, there is a problem that the activity of the titanium compound is high, and modified polymers and aggregated foreign matter are generated during the polyester polymerization reaction. In the method described in Patent Document 3, there are problems that the germanium compound promotes the decomposition of the polyester resin, resulting in the generation of gelled matter, and the heat resistance of the obtained film is deteriorated. In addition, in the method described in Patent Document 4, there are problems with the recycle durability of the polyester resin itself, so that the recycle ratio cannot be increased, and it cannot be applied to optical films that require high quality.

[0009] The present invention aims to solve these problems and provide a highly transparent polyester film that produces little foreign matter such as gelled matter even when remelted, has heat resistance, and can maintain extremely high quality even when recycled, as well as a method for producing the same. [Means for solving the problem]

[0010] The present invention aims to solve the above problems. (1) A polyester film having a base layer mainly composed of a polyester resin, an internal haze of 0.5% or less, and satisfying all of the following formulas (I) to (IV): 5ppm≦Germanium element content (by mass)≦80ppm (I) 5ppm≦Manganese element content (by mass)≦40ppm (II) 4ppm≦Sodium content (by mass)≦40ppm (III) 14ppm≦Metal element content (mass basis)≦100ppm (IV) (2) The polyester film according to (1), wherein the content of phosphorus in the base layer is 15 ppm or more and 70 ppm or less by mass. (3) The polyester film according to (2), wherein at least a part of the phosphorus element is derived from phosphoric acid and sodium phosphate. (4) The polyester film according to any one of (1) to (3), wherein the base layer has a melt resistivity of 10.0 MΩ·cm or less. (5) The polyester film according to any one of (1) to (4), which has a coating layer on at least one surface of the base layer. (6) The polyester film according to any one of (1) to (5), wherein the base layer contains recycled materials. (7) The polyester film according to (6), wherein the recycled materials include self-recovered materials. (8) The polyester film according to (6) or (7), wherein the base layer is made from the recycled raw materials and has a recycle index (R) calculated by the following formula (V) of 1.5 or more: [Recycling Index (R)] R = Σ(m n *r n ) (V) n: Type of raw material contained in the base layer m n : Mass ratio of each raw material in the recycled base material layer r n : Recycling index for each material defined as follows Non-recovered materials: 1.0 Recovered raw materials: The value obtained by adding 1.0 to the recycling index of the recovered compacts (9) A method for producing the polyester film according to any one of (6) to (8), characterized in that a recycled raw material obtained by removing a coating layer from a polyester film having a coating layer is used. Effect of the Invention

[0011] According to the present invention, it is possible to provide a highly transparent polyester film which generates little foreign matter such as gelled matter even when remelted, has heat resistance, and can maintain extremely high quality even when recycled, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. The polyester film of the present invention is a polyester film having a base layer mainly composed of a polyester resin, an internal haze of 0.5% or less, and satisfying all of the following formulae (I) to (IV). 5ppm≦Germanium element content (by mass)≦80ppm (I) 5ppm≦Manganese element content (by mass)≦40ppm (II) 4ppm≦Sodium content (by mass)≦40ppm (III) 14ppm≦Metal element content (mass basis)≦100ppm (IV).

[0013] The polyester film of the present invention has a base layer mainly composed of a polyester resin. In the present invention, the polyester resin refers to a resin having a molecular structure in which dicarboxylic acid units and diol units are repeatedly linked by ester bonds, and the polyester film refers to a sheet-shaped molded body mainly composed of a polyester resin. Details of polyester resins that can be suitably used for the polyester film of the present invention will be described later. The main component refers to a component that is contained in an amount of more than 50 mass% to 100 mass% or less when the total components of the target object are taken as 100 mass%. The base layer mainly composed of a polyester resin refers to a layer that is mainly composed of a polyester resin and has a thickness of 10 μm or more (hereinafter, the "base layer mainly composed of a polyester resin" may be simply referred to as the "base layer"). The base layer may have a single layer structure or a laminate structure, and when layers that satisfy the above requirements are laminated in succession, the entirety of these layers is treated as one base layer.

[0014] The base layer in the polyester film of the present invention must contain germanium element in an amount of 5 ppm to 80 ppm by mass. The lower limit is preferably 10 ppm. The upper limit is preferably 60 ppm, more preferably 50 ppm. The germanium compound is used as a polymerization catalyst for polyester resin, and by setting the amount to the above lower limit or more, it is possible to proceed with the polycondensation reaction without delay, and the generation of foreign matter can be reduced. In addition, the germanium element has excellent catalytic activity, and if it is present in excess, it contributes to thermal decomposition, oxidative decomposition, and hydrolysis of the polyester resin. Therefore, by satisfying the amount of germanium element below the above upper limit, it is possible to suppress various decompositions of the polyester resin. The method for measuring the amount of germanium element in the base layer will be described later (the same applies to the amounts of other elements). Here, the mass basis means that the total components constituting the polyester film are used as the basis, and can be interpreted in the same manner hereinafter.

[0015] The base layer in the polyester film of the present invention must contain manganese element in an amount of 5 ppm to 40 ppm by mass. The lower limit is preferably 10 ppm. The upper limit is preferably 30 ppm. Since manganese compounds affect the thermal decomposition of polyester resins, the heat resistance of polyester films can be improved and the generation of foreign matter can be reduced by making the amount of manganese equal to or greater than the lower limit. In addition, manganese element has high catalytic activity even in heat treatment at a relatively low temperature below the melting point of polyester resins, such as in a film stretching process, and contributes to the thermal decomposition, oxidative decomposition, and hydrolysis of polyesters. Therefore, by satisfying the amount of manganese element equal to or less than the upper limit, it is possible to suppress various decompositions of polyester resins and films during processing.

[0016] The base layer in the polyester film of the present invention must contain sodium element in an amount of 4 ppm or more and 40 ppm or less by mass. The upper limit is preferably 30 ppm, more preferably 20 ppm. By keeping the sodium element in the above range, the generation of foreign matter caused by sodium element is reduced, heat resistance is improved, and various decompositions of the polyester resin and film caused by thermal decomposition can be suppressed.

[0017] In addition, the base layer in the polyester film of the present invention has a total content of metal elements of 14 ppm or more and 100 ppm or less, preferably 80 ppm or less, based on mass. If the amount of metal elements in the base layer exceeds 100 ppm, the polyester chain is promoted to be cut in the melt extrusion process, so that gelled matter having a three-dimensional structure is likely to occur frequently, which becomes a defect of the film and reduces the quality. In addition, there is also a problem that defects in the film are increased due to precipitation of the metal component itself or a complex of the metal component and other chemical substances. In addition, the metal element here is synonymous with the metal element generally defined, and refers to all elements of Groups 1, 2 to 12 except hydrogen in the periodic table of elements, Groups 13 from the third period onwards except boron, Groups 14 from the fourth period onwards except carbon and silicon, Groups 15 from the fifth period onwards, and Group 16 of the sixth period. In addition, the lower limit of the metal element content in the base layer of the polyester film is substantially 14 ppm from the lower limit of the content of germanium element, manganese element, and sodium element.

[0018] The base layer in the polyester film of the present invention preferably contains phosphorus element in an amount of 15 ppm or more and 70 ppm or less by mass. The lower limit is more preferably 20 ppm, even more preferably 25 ppm, and particularly preferably 30 ppm. The upper limit is preferably 60 ppm, more preferably 50 ppm. By setting the content within the above range, heat resistance can be imparted to the polyester, and the productivity can also be improved.

[0019] In the base layer of the polyester film of the present invention, metal elements that are likely to cause foreign matter are not contained as much as possible, and heat resistance is imparted to the polyester by adding a compound containing manganese and sodium elements or a phosphorus compound. In particular, for sodium and phosphorus elements, phosphoric acid and sodium phosphate salts are preferably used from the viewpoint of suppressing deterioration of the polyester resin. That is, in the polyester film of the present invention, at least a part of the phosphorus element contained in the base layer is preferably derived from at least one of phosphoric acid and sodium phosphate. Note that, when phosphate ions and sodium ions or sodium phosphate are present in the base layer, the phosphorus element contained in the base layer is considered to be "derived from at least one of phosphoric acid and sodium phosphate".

[0020] In order to enhance the effect of suppressing deterioration (hydrolysis resistance) of the polyester resin of the base layer, it is preferable to add phosphoric acid and sodium phosphate to the polyester resin that is the raw material of the base layer, and it is more preferable to make the contents of these components closer to equal amounts in terms of molar ratio. That is, in the polyester film of the present invention, it is preferable that the base layer contains both phosphorus element derived from phosphoric acid and phosphorus element derived from sodium phosphate, and it is more preferable to make the amounts of both closer to equal amounts in terms of molar ratio.

[0021] In the polyester film of the present invention, from the viewpoint of achieving both reduction of thickness unevenness of the polyester film and improvement of productivity, the melt resistivity of the base layer is preferably 10.0 MΩ·cm or less. One of the factors that affect the thickness unevenness of the polyester film obtained by the melt casting method is the electrostatic applicability when the molten sheet-like material for obtaining the base layer is cooled and solidified on a cast drum. This electrostatic applicability can be evaluated by the melt resistivity when the base layer of the finally obtained polyester film is melted, and can also be substituted by the melt resistivity of the molten polyester resin that is the raw material of the base layer.

[0022] The melt resistivity is the volume resistivity of the heat-melted polyester film (or polyester resin composition). From the above viewpoint, the melt resistivity of the base layer of the polyester film of the present invention is preferably 10.0 MΩ·cm or less, more preferably 5.0 MΩ·cm or less. When the melt resistivity of the base layer is 10.0 MΩ·cm or less, the electrostatic applicability is good during cooling and solidification in the cast drum, so that the thickness unevenness of the obtained polyester film is suppressed, and the film production speed can be increased to improve productivity. In addition, the lower limit of the melt resistivity of the base layer is not particularly limited, but is 0.1 MΩ·cm from the viewpoint of feasibility. The melt resistivity of the base layer of the polyester film can be measured by the following method (the details of the measurement method will be described later). First, the crushed polyester film (if it has a coating layer, the coating layer is removed and then crushed) is vacuum-dried at 180°C for 3 hours, and then melted at 290°C. Then, an electrode is made by placing a Teflon (registered trademark) spacer between two copper plates, and this electrode is immersed in the obtained molten resin. A voltage of 5000 V (V) is applied between the electrodes, and the voltage (V') is measured. The melt resistivity value (ρ) is calculated using the following formula. ρ(Ω cm)=V S R / (I V') In the formula, V is the applied voltage (V), S is the electrode area (cm 2 ), R: resistor resistance (Ω), I: distance between electrodes (cm), V': measured voltage (V).

[0023] The method of making the melt resistivity of the base layer within the above range includes, but is not limited to, making the metal element content or phosphorus element content in the polyester resin composition that is the raw material of the base layer within the above-mentioned preferred range, and adding particles or compounds that are responsible for electrical conduction to the raw material. However, if the metal element content in the raw material is increased, as described above, the heat resistance of the resulting polyester film may be reduced or the generation of foreign matter due to gelation may be induced. Therefore, it is preferable to apply an ionic substance that is not based on metal, and for example, sulfonium compounds, phosphonium compounds, ammonium compounds, imidazolium compounds, pyridinium compounds, and pyrrolidinium compounds can be selected as cationic substances, and sulfonate compounds, phosphate compounds, sulfate compounds, acetate compounds, imide compounds, and the like can be selected as anionic substances. In particular, neutralized salts of phosphonium compounds and sulfonate compounds are preferred.

[0024] The polyester resin, which is the main component of the base layer in the polyester film of the present invention, is preferably polyethylene terephthalate (PET) in order to sufficiently increase heat resistance. In addition, a copolymer component may be contained within a range that does not impair the effects of the present invention. Polyethylene terephthalate refers to a polyester resin whose main structural unit is an ethylene terephthalate unit, and the main structural unit refers to a structural unit contained in more than 50 mol% when all structural units constituting the molecular chain of the resin are 100 mol%. Note that the same can be interpreted for other polyester resins below, except that the main structural unit is replaced.

[0025] Next, a method for producing the polyester resin composition used in the base layer of the polyester film according to the present invention will be described. The method for producing the polyester resin composition uses a dicarboxylic acid component or its ester and a diol component as main raw materials and consists of the following two-stage process: (A) an esterification reaction or (B) an ester exchange reaction as the first stage, followed by (C) a polycondensation reaction as the second stage.

[0026] As raw materials for producing the polyester resin composition used in the base layer of the polyester film of the present invention, dicarboxylic acids or dicarboxylic acid esters and diols can be used, and these can also be used in combination of two or more kinds.

[0027] Examples of dicarboxylic acid components that can be used in the production of the polyester resin composition include terephthalic acid, 2,6-naphthalenedicarboxylic acid, isophthalic acid, diphenyl-4,4'-dicarboxylic acid, 5-sodium sulfoisophthalic acid, oxalic acid, succinic acid, adipic acid, sebacic acid, malonic acid, and dimer acid. Examples of dicarboxylic acid esters include the lower alkyl esters, acid anhydrides, and acyl chlorides of the above-mentioned dicarboxylic acids, and methyl esters, ethyl esters, and hydroxyethyl esters are preferably used. These components may be used alone or in combination.

[0028] In the polyester resin composition used in the base layer of the polyester film of the present invention, more preferred embodiments of the dicarboxylic acid or dicarboxylic acid ester are terephthalic acid, 2,6-naphthalenedicarboxylic acid, isophthalic acid, or alkyl esters thereof, in that a polyester resin composition having a high melting point and which can be easily processed into a film can be obtained, and these can also be used in appropriate combinations.

[0029] Examples of diols that can be used in the production of the polyester resin composition include aliphatic diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, butanediol, 2-methyl-1,3-propanediol, hexanediol, and neopentyl glycol; alicyclic diols include saturated alicyclic primary diols such as cyclohexanedimethanol, cyclohexanediethanol, norbornanedimethanol, norbornanediethanol, tricyclodecane dimethanol, tricyclodecane diethanol, decalin dimethanol, and decalin diethanol; and saturated heterocyclic primary diols containing cyclic ethers such as isosorbide. Other examples include various alicyclic diols such as cyclohexanediol, bicyclohexyl-4,4'-diol, 2,2-bis(4-hydroxycyclohexylpropane), 2,2-bis(4-(2-hydroxyethoxy)cyclohexyl)propane, cyclopentanediol, 3-methyl-1,2-cyclopentadiol, 4-cyclopentene-1,3-diol, and adamantanediol, and aromatic diols such as paraxylene glycol, bisphenol A, bisphenol S, styrene glycol, 9,9-bis(4-(2-hydroxyethoxy)phenyl)fluorene, and 9,9'-bis(4-hydroxyphenyl)fluorene.

[0030] These components may be used alone or in combination, and polyfunctional alcohols such as trimethylolpropane and pentaerythritol may also be used other than the diol within the scope of the invention without impairing the effects of the invention. It is preferable to use ethylene glycol as the diol, since it is possible to fully achieve the effects of the invention and to obtain a polyester resin composition that is easily processed into a film.

[0031] In the manufacturing method of the polyester resin composition used in the base layer of the polyester film of the present invention, the (A) esterification reaction step in the first step is a step of esterifying a dicarboxylic acid with a diol at a predetermined temperature until a predetermined amount of water is distilled to obtain a low polymer. When obtaining a low polymer by esterification reaction, the molar ratio of dicarboxylic acid to diol (diol / dicarboxylic acid) before the start of esterification reaction is preferably in the range of 1.05 to 1.40 from the viewpoint of esterification reactivity and heat resistance. More preferably, it is 1.05 to 1.30, and even more preferably, it is 1.05 to 1.20. By setting it in the above range, it has good reactivity and can suppress the generation of by-products such as dimers of diol, so that heat resistance can be improved.

[0032] The (B) transesterification step is a step of transesterifying a dicarboxylic acid alkyl ester with a diol until a predetermined amount of alcohol is distilled to obtain a low polymer. When a low polymer is obtained by transesterification, the molar ratio of the dicarboxylic acid alkyl ester to the diol (diol / dicarboxylic acid alkyl ester) is preferably in the range of 1.7 to 2.3 from the viewpoints of reactivity and heat resistance. By setting the ratio in the above range, the transesterification reaction can be efficiently progressed and the by-production of a dimer of the diol can be suppressed, thereby improving the heat resistance.

[0033] In the second step, the polycondensation reaction (C) is a step for obtaining a polyester resin composition from the low polymer obtained by the esterification reaction (A) or the transesterification reaction (B).

[0034] The polyester resin composition used in the base layer of the polyester film of the present invention can be produced by any of batch polymerization, semi-continuous polymerization, and continuous polymerization.

[0035] In the method for producing the polyester resin composition used in the base layer, the catalyst used in the (A) esterification reaction may be a compound such as manganese, cobalt, zinc, titanium, or calcium, but it is preferable to carry out the esterification reaction without a catalyst from the viewpoint of thermal decomposition and generation of foreign matter in the polycondensation reaction stage. Here, the (A) esterification reaction proceeds sufficiently even without a catalyst due to the self-catalytic action of the carboxylic acid. In addition, a known transesterification catalyst can be used as the catalyst used in the (B) transesterification reaction. Examples of the transesterification catalyst include organic manganese compounds, organic magnesium compounds, organic calcium compounds, organic cobalt compounds, and organic lithium compounds, and specifically include carbonates, acetates, benzoates, oxides, and hydroxides, but are not limited thereto.

[0036] In the method for producing the polyester resin composition used in the base layer of the polyester film of the present invention, the compound containing germanium, manganese and sodium may be added at any stage of the (A) esterification reaction or (B) ester exchange reaction process, or the subsequent (C) polycondensation reaction process. However, by adding the compound before the end of the polycondensation reaction, it is possible to obtain a polyester resin composition having improved heat resistance and reduced foreign matter.

[0037] In the method for producing a polyester resin composition of the present invention, it is preferable to add a compound containing germanium, manganese and sodium elements before the end of the polycondensation reaction, and to have the content thereof satisfy the following formulas (VI) to (VIII) with respect to the finally obtained polyester resin. By adopting such an embodiment, it becomes easy for the base layer of the obtained polyester film to satisfy the formulas (I) to (IV). When the base layer is produced by mixing another resin with the polyester resin, in the following formulas (VI) to (VIII), "mass ratio relative to the polyester resin" is interpreted as "mass ratio relative to the polyester resin composition for producing the base layer". 5ppm≦Germanium content (mass ratio to polyester resin)≦80ppm (VI) 5ppm≦Manganese element content (mass ratio to polyester resin)≦40ppm (VII) 4 ppm or less sodium element content (mass ratio to polyester resin) ≦ 40 ppm (VIII).

[0038] In the method for producing a polyester resin for a base layer, it is necessary to add germanium element so that the content is 5 ppm or more and 80 ppm or less relative to the mass of the polyester resin. The lower limit is preferably 10 ppm. The upper limit is preferably 60 ppm, more preferably 50 ppm. The germanium compound is used as a polymerization catalyst for polyester, and by setting the content to the above lower limit or more, it is possible to proceed with the polycondensation reaction without delay. In addition, the germanium element has excellent catalytic activity, and if it is present in excess, it contributes to thermal decomposition, oxidative decomposition, and hydrolysis of polyester. Therefore, by satisfying the amount of germanium element below the above upper limit, it is possible to suppress various decompositions of polyester. Examples of compounds containing germanium element used in the production of polyester resin include, but are not limited to, germanium oxide and germanium alkoxide. It is possible to use these compounds alone or in combination of multiple types.

[0039] The polyester resin composition for the base layer must contain manganese element in an amount of 5 ppm to 40 ppm relative to the mass of the polyester resin. The lower limit is preferably 10 ppm. The upper limit is preferably 30 ppm. By making the manganese element amount equal to or greater than the lower limit, it is possible to improve the heat resistance of the polyester resin. In addition, manganese element has high catalytic activity even in heat treatment at a relatively low temperature below the melting point of the polyester resin, such as in a film stretching process, and contributes to thermal decomposition, oxidative decomposition, and hydrolysis of the polyester. Therefore, by satisfying the manganese element amount equal to or less than the upper limit, it is possible to suppress various decompositions of the polyester resin during processing.

[0040] The compound containing manganese element used in the production of the polyester resin composition is not particularly limited, but examples thereof include manganese acetate, manganese nitrate, manganese chloride, manganese sulfate, and hydrates thereof, and manganese acetate is preferred from the viewpoint of solubility and catalytic activity. These compounds can be used alone or in combination. The form of the compound containing manganese element when added may be any of powder, slurry, and solution, and it is preferred to add it as a solution from the viewpoint of dispersibility. The solvent at this time is preferably the same as the diol component of the polyester resin composition. For example, in the case of PET, it is particularly preferred to use ethylene glycol as the solvent.

[0041] In addition, the polyester resin composition for the base layer needs to contain sodium element in an amount of 4 ppm or more and 40 ppm or less relative to the mass of the polyester resin. The upper limit is preferably 30 ppm, more preferably 20 ppm. If the sodium element content exceeds 40 ppm, the amount of metal agglomerates increases and the heat resistance of the polyester resin deteriorates. If the sodium element content is below 4 ppm, the heat resistance of the polyester resin deteriorates. By setting the sodium element content within the above range, the heat resistance is improved and the deterioration of the polyester resin caused by thermal decomposition can be suppressed.

[0042] The compound containing sodium element used in the production of the polyester resin composition is not particularly limited. For example, sodium phosphate, hydroxide, acetate, carbonate, nitrate, chloride, etc. can be used. From the viewpoint of heat resistance, the compound containing sodium element is more preferably sodium phosphate. Examples of sodium phosphate include sodium dihydrogen phosphate, disodium hydrogen phosphate, and trisodium phosphate. From the viewpoint of heat resistance, sodium dihydrogen phosphate is particularly preferable. In addition, a plurality of sodium phosphates may be used in combination.

[0043] In the production of the polyester resin composition for the base layer, it is preferable to use the sodium phosphate in combination with another compound containing phosphorus, and it is particularly preferable to mix the sodium phosphate and phosphoric acid as a buffer solution. By adding the sodium phosphate and phosphoric acid as a buffer solution, it is possible to achieve better heat resistance.

[0044] In addition, an alkali metal compound other than sodium phosphate may be used in combination within the range of the above-mentioned sodium element content. For example, by using potassium hydroxide in combination, the melt resistivity of polyester required for electrostatic application film formation in film production can be reduced, thereby improving productivity.

[0045] The compound containing sodium element may be added in any form such as powder, slurry, or solution, and is preferably added as a solution from the viewpoint of dispersibility. The solvent used in this case is preferably the same as that of the diol component of the polyester resin composition, and in the case of PET, ethylene glycol is particularly preferred.

[0046] The polyester resin for the base layer is preferably added with phosphorus element so that the content is 15 ppm or more and 70 ppm or less relative to the mass of the polyester resin. The lower limit is preferably 20 ppm, more preferably 25 ppm. The upper limit is preferably 60 ppm, more preferably 50 ppm. By setting the content within the above range, heat resistance can be imparted to the polyester resin.

[0047] In the method for producing a polyester resin composition for a base layer, it is preferable to further deactivate the polyester resin composition obtained after the polycondensation reaction. It is known that the catalytic activity of a polyester resin composition obtained by polycondensation reaction using a germanium catalyst is deactivated by treating the composition under relatively mild conditions such as hot water. By losing the catalytic activity, when the polyester resin composition is used in the subsequent film formation process, the thermal decomposition caused by the polycondensation catalyst is suppressed, and a polyester film with excellent heat resistance can be obtained.

[0048] The deactivation treatment of the polyester resin composition can be carried out with various solutions such as water, phosphorus compounds, and ammonia compounds. Examples of phosphorus compounds include, but are not limited to, phosphate esters such as trimethyl phosphate, triethyl phosphate, tributyl phosphate, triphenyl phosphate, dimethyl phosphate, diphenyl phosphate, methyl phosphate, and ethyl phosphate, and aqueous solutions or solutions of phosphorus compounds such as phosphoric acid and polyphosphoric acid, and the polyester resin composition is contacted with the polyester resin composition. Examples of ammonia compounds include triethylamine, tetraethylammonium hydroxide, and tetra-n-butylammonium hydroxide. The temperature at which the polyester resin composition is contacted with these treatment solutions and treated is preferably 20°C or higher and 120°C or lower, more preferably 40°C or higher and 100°C or lower, and even more preferably 50°C or higher and 100°C or lower. The treatment time is preferably 30 minutes or longer and 24 hours or shorter, more preferably 1 hour or longer and 12 hours or shorter.

[0049] In the method for producing the polyester resin composition for the base layer, for example, germanium element and phosphorus element are distilled off during the polycondensation reaction, so it is preferable to adjust the addition amount taking into consideration the distilled amount so as to obtain the above-mentioned element amount.

[0050] In the method for producing a polyester resin composition for a base layer, when the method is carried out via (A) esterification reaction, it is preferable to add a glycol component such as ethylene glycol after the esterification reaction and before adding a compound containing sodium element. More preferably, it is added after the compound containing manganese element and before adding a compound containing sodium element. Since the low molecular weight substance of the polyester resin composition obtained by the esterification reaction has a higher degree of polymerization than the low molecular weight substance obtained by the transesterification reaction, when a sodium phosphate salt is used, it is difficult to disperse and is prone to foreign matter formation. Therefore, foreign matter formation can be suppressed by adding a glycol component such as ethylene glycol and lowering the degree of polymerization by depolymerization. At this time, if a compound containing manganese element is present, depolymerization can be performed more efficiently.

[0051] The amount of glycol components such as ethylene glycol to be added is preferably 0.05 to 0.5 times by mol relative to the total amount of acid components, and more preferably 0.1 to 0.3 times by mol. By adjusting the amount within the above range, the polymerization time is not delayed due to a temperature drop in the polymerization system, and the sodium phosphate salt can be prevented from becoming a foreign substance.

[0052] During and after the addition of the compounds containing germanium, manganese and sodium, it is preferable to stir the reaction system, as stirring can disperse the additives more uniformly.

[0053] In addition, in the method for producing a polyester resin composition for a base layer, solid-phase polymerization may be performed to obtain a polyester resin composition having a high molecular weight. The solid-phase polymerization is performed by heating the polyester resin composition under an inert gas atmosphere or under reduced pressure, although the apparatus and method are not particularly limited. The inert gas may be any gas inert to the polyester resin composition, such as nitrogen, helium, and carbon dioxide, but nitrogen is preferably used from the viewpoint of economy. In addition, under reduced pressure conditions, it is advantageous to achieve a higher vacuum because it shortens the time required for the solid-phase polymerization reaction, and specifically, it is preferable to maintain the pressure at 110 Pa or less. In addition, when performing a deactivation treatment, it is preferable to perform it after the solid-phase polymerization in order to efficiently perform the solid-phase polymerization.

[0054] When the polyester resin composition is processed into a base layer of a polyester film, one or more of various additives, such as colorants including pigments and dyes, lubricants, antistatic agents, flame retardants, ultraviolet absorbers, antibacterial agents, nucleating agents, plasticizers, and release agents, may be added within a range that does not impair the effects of the present invention.

[0055] Specific examples of the polyester resin composition for obtaining the base layer of the polyester film of the present invention and the method for producing the base layer will be given below, but the present invention is not limited thereto.

[0056] A slurry of terephthalic acid and ethylene glycol (1.15 times the molar amount of terephthalic acid) is gradually added to an esterification reactor containing dissolved bishydroxyethyl terephthalate (BHT) at 240-260°C to allow the esterification reaction to proceed. The temperature in the reaction system is controlled to 245-250°C, and the esterification reaction is terminated when the reaction rate reaches 95%.

[0057] The esterification product thus obtained is transferred to a polymerization apparatus, and a manganese compound and a germanium compound are added. Then, ethylene glycol is added, and phosphoric acid and sodium phosphate are added. During these operations, it is preferable to keep the temperature in the system at 240 to 255°C so that the esterification product does not solidify.

[0058] Thereafter, the temperature inside the polymerization apparatus is gradually increased to 260 to 300° C., while the pressure inside the polymerization apparatus is gradually reduced from normal pressure to 133 Pa or less to distill off ethylene glycol. The reaction is terminated when a predetermined stirring torque is reached, the reaction system is returned to normal pressure with nitrogen gas, and the molten polyester is discharged into cold water in the form of strands and cut to obtain a polyester resin composition.

[0059] The polyester resin composition thus obtained has excellent heat resistance and produces little gel composition or low molecular weight substances such as terephthalic acid during melt molding or processing, and can be suitably used for polyester films that require high quality, particularly for optical film applications, i.e., the base layer of the polyester film of the present invention.

[0060] The base layer in the polyester film of the present invention is not particularly limited as long as it is mainly composed of polyester resin, but is preferably a biaxially oriented polyester film. The term "biaxial orientation" as used herein refers to a film that shows a biaxially oriented pattern in wide-angle X-ray diffraction. A biaxially oriented polyester film can generally be obtained by stretching an unstretched polyester sheet by about 2.5 to 5.0 times in each of the longitudinal and transverse directions of the sheet, and then subjecting the sheet to heat treatment to complete the crystal orientation. The longitudinal direction refers to the direction in which the film runs during the manufacturing process (in the case of a film roll, this corresponds to the winding direction, also called the vertical direction), and the transverse direction (also called the horizontal direction) refers to the direction perpendicular to the longitudinal direction within the film plane.

[0061] The base layer in the polyester film of the present invention is obtained by melt-extruding a resin composition mainly composed of a polyester resin and forming it into a sheet. The base layer of the polyester film of the present invention may be composed of one layer in the thickness direction, or may have multiple layers. A base layer having multiple layers can be obtained, for example, by supplying molten polyester resin compositions from multiple extruders, stacking them in the thickness direction, and then cooling and solidifying them to form a sheet.

[0062] The base layer in the polyester film of the present invention has an internal haze of 0.5% or less, preferably 0.3% or less. Haze is a value indicating the proportion of light scattered through the polyester film, and the lower the haze, the less light is scattered, and the polyester film has a more transparent and clear appearance. Light scattering is mainly divided into scattering due to the surface shape of the polyester film (external scattering) and scattering due to additives, impurities, cavities, etc. inside the polyester film (internal scattering), and the scattering ratio due to the former is called external haze, and the scattering ratio due to the latter is called internal haze. Note that internal haze can be measured with a known haze meter, the details of which will be described later.

[0063] Optical films used in displays and the like have various processing such as a hard coat layer, an electrode layer, a refractive index adjustment layer, and a transparent adhesive layer on their surfaces, so that the external haze, which is scattering due to the surface shape, can be adjusted by the processing configuration. On the other hand, the internal haze caused by internal scattering cannot be adjusted by processing, so it is a very important characteristic for an optical substrate film. Therefore, if the internal haze of the film exceeds 0.5%, the proportion of light transmitted through the polyester film that is scattered increases, and the transparency and definition of the display deteriorate.

[0064] As a method for adjusting the internal haze to a desired value, a method for preventing the inclusion of foreign matter that scatters light, such as additives, impurities, and air bubbles, inside the film, or a method for properly controlling the crystallinity of the polyester film by biaxial orientation can be used. More specifically, this can be achieved by setting the amount of additives, particularly metal elements such as catalysts, in the polyester resin composition used in the base layer to 100 ppm or less, preferably 80 ppm or less, or by using a specific catalyst type or phosphorus-based additive in an appropriate amount as described above. In addition, other preferred methods include properly storing and weighing the polyester resin composition to prevent the inclusion of foreign matter, and performing high-precision filtration with a filtration accuracy of 10 μm or less during the melt extrusion process of the polyester resin. These methods can be used in appropriate combination.

[0065] In the polyester film of the present invention, when additives such as lubricants are used for the purpose of reducing the slip coefficient and improving the handling, it is preferable to reduce the amount of additives as much as possible. As a method for efficiently reducing the slip coefficient with a small amount of additives, it is preferable to localize the additives on the film surface as much as possible. Specifically, a method in which a base layer is configured by laminating multiple layers in the thickness direction and an additive is added only to the layer forming the film surface, or a method in which a coating layer containing an additive is provided on the polyester base layer, etc. can be mentioned. In particular, it is preferable that the polyester film of the present invention has a coating layer on at least one surface of the base layer, since it is possible to relatively easily add functions such as improving adhesion with a functional layer provided on the polyester film and imparting antistatic properties.

[0066] In the polyester film of the present invention, the method for laminating the coating layer is not particularly limited. For example, a so-called off-line coating method can be used in which a coating layer is formed by unwinding a film, coating and drying the film in a separate process from the film production process, or a so-called in-line coating method can be used in which a resin is extruded by an extruder, the resin is formed into a sheet-like film, and coating is performed during the film production process to obtain a coated film in one go.

[0067] It is preferable to add a lubricant to the coating layer of the present invention in order to improve the slipperiness of the film surface and improve the handling. The lubricant used is not particularly limited as long as it does not impair the film properties, but examples thereof include inorganic particles such as colloidal silica, titanium oxide, aluminum oxide, zirconium oxide, calcium carbonate, carbon black, and zeolite particles, and organic particles such as acrylic particles, silicone particles, polyimide particles, "Teflon" (registered trademark) particles, crosslinked polyester particles, crosslinked polystyrene particles, crosslinked polymer particles, and core-shell particles. Any of these particles may be used, or a combination of two or more types may be used. The number average primary particle size of these particles (hereinafter, sometimes simply referred to as the average primary particle size) is preferably within the range of 50 to 1000 nm. Here, the average primary particle size is the average particle size of primary particles defined in JIS H7008 (2002) as particles generated by the growth of a single crystal nucleus. The amount of particles added should be appropriately adjusted and designed depending on the thickness of the lubrication layer, resin composition, average primary particle size, desired lubricity, and application, but is preferably in the range of 0.05 to 8 mass%, and more preferably in the range of 0.1 to 5 mass%, when the total components forming the lubrication layer are taken as 100 mass%.

[0068] The coating layer of the polyester film of the present invention may contain known polyester, acrylic, urethane, epoxy, and other resins, either alone or in combination, in order to provide various functions such as retaining lubricant particles, improving adhesion to other functional layers, and sealing oligomers precipitated from the film. Furthermore, the coating layer may contain a melamine, oxazoline, or carbodiimide crosslinking agent.

[0069] Next, the method for producing the polyester film of the present invention will be explained using an example in which polyethylene terephthalate (PET) is used as the polyester resin forming the base layer, but the polyester film of the present invention is not limited to those produced by the following method.

[0070] PET pellets with an intrinsic viscosity of 0.500 to 0.800 dl / g constituting the polyester film for the base layer are dried, fed to an extruder, and melted at 260 to 300°C. Next, after removing foreign matter from the molten resin with a filter, the resin is extruded into a sheet from a T-shaped die, and wound around a mirror-finished casting drum with a surface temperature of 10 to 60°C using an electrostatic casting method, and cooled and solidified to produce an unstretched PET film. This unstretched film is stretched 2.5 to 5.0 times in the longitudinal direction between rolls heated to 70 to 100°C to obtain a uniaxially stretched film. Note that a part or all of the PET pellets may contain recycled raw materials, which will be described later. In addition, when stretching in the longitudinal direction, the temperature of the uniaxially stretched film may be adjusted by heating from above and below using a radiation heater, if necessary.

[0071] A water-based coating agent constituting a coating layer is applied to at least one side of this uniaxially stretched film. Then, the widthwise ends of the uniaxially stretched film coated with the water-based coating agent are held by clips of a tenter device and introduced into a drying zone, where the coating agent is dried and then heated at a temperature of 70 to 150°C, and then continuously stretched 2.5 to 5.0 times in the transverse direction in a heating zone of 70 to 150°C, followed by heat treatment for 5 to 40 seconds in a heating zone of 200 to 240°C, and passing through a cooling zone of 100 to 200°C to obtain a polyester film in which a coating layer is laminated on a substrate layer in which crystal orientation has been completed. During the heat treatment, a 3 to 12% relaxation treatment may be performed as necessary. In the above example, the biaxial stretching is performed by sequential longitudinal and transverse stretching, but the stretching may be performed by simultaneous biaxial stretching, and after longitudinal and transverse stretching, the stretching may be performed again in either the longitudinal or transverse direction. However, in the case of simultaneous biaxial stretching, since it is not possible to apply a water-based coating material to a uniaxially stretched film, when an in-line coating method is employed, it is advisable to apply a water-based coating material to an unstretched film.

[0072] Thereafter, both ends in the width direction held by the clips are cut and removed from the obtained polyester film, and the film is cut to a desired width and wound up. Note that the cutting and removal of both ends in the width direction and the cutting to a desired width can be performed by a device capable of cutting a traveling film parallel to the longitudinal direction, such as a known slitter.

[0073] In terms of reducing energy consumption and CO2 generation, the polyester film of the present invention preferably contains a recycled raw material in the base layer, and more preferably contains a self-recovered raw material. Here, the recycled raw material refers to a recycled polyester raw material obtained by regenerating a part of a polyester film that was not made into a product during the manufacturing process, or a polyester film or a polyester molded body after use. When using a recycled raw material derived from a polyester film, the recycled raw material can be used to manufacture a base layer of the same polyester film, or a base layer of a different polyester film. When a base layer of the same polyester film is manufactured using a recycled raw material derived from a polyester film, the recycled raw material is called a self-recovered raw material. Note that, when a base layer of the same polyester film is manufactured using a recycled raw material, there is a possibility that a slight difference in composition occurs compared to when a recycled raw material is not used, but if the composition of the base layer of the polyester film from which the recycled raw material is derived and the base layer of the resulting polyester film are 95% or more the same on a mass basis, the two are treated as "base layers of the same polyester film".

[0074] In recent years, with the rise in environmental awareness, there is a strong demand for reducing energy consumption and CO2 emissions, and in order to achieve this, it is effective to use recycled materials for the base layer of polyester film. In particular, to realize a recycling-oriented society, it is preferable to use recycled materials regenerated from the film itself, i.e., self-recovered materials.

[0075] The polyester film of the present invention has a base layer made of recycled materials, and preferably has a recycle index (R) calculated by the following formula (V) of 1.5 or more, more preferably 2.0 or more. Such a polyester film can be obtained by incorporating recycled materials in the polyester resin raw material constituting the base layer. [Recycling Index (R)] R = Σ(m n *r n ) (V) n: Type of raw material contained in the base layer m n : Mass ratio of each raw material in the recycled base material layer r n : Recycling index for each material defined as follows Non-recovered materials: 1.0 Recovered raw materials: The value calculated by adding 1.0 to the recycling index of the recovered molded bodies.

[0076] The recycle index (R) is a value indicating the recycle index of the base layer of the polyester film, specifically, the average number of times the polyester resin raw material constituting the base layer of the polyester film of the present invention is used. The recycle index (R) of the base layer made of polyester resin containing no recycled raw material is 1.0, and the recycle index of the recycled raw material obtained by recovering and regenerating this polyester film is 2.0, which is 1.0 plus 1.0, the recycle index (R) of the base layer of the polyester film before regeneration. Therefore, the recycle index (R) of the base layer of the polyester film made of 100% of the recycled raw material is 2.0, which means that it has been filmed twice as a polyester resin raw material. In addition, when the entire polyester resin is taken as 100% by mass, the recycle index (R) of the base layer of the polyester film made of 50% by mass of non-recycled raw material (raw material recycle index r1: 1.0) and 50% by mass of the recycled raw material (raw material recycle index r2: 2.0) is calculated to be 1.5 by formula (V). This means that the polyester resin constituting the base layer is used 1.5 times on average.

[0077] The higher the recycle index (R) of the base layer of the polyester film, the better in terms of reducing the environmental load. However, in the case of highly transparent and high-quality polyester films, problems such as gel generation due to decomposition of polyester resin, discoloration of the resin, and aggregation of added metal components occur when used repeatedly, and these issues must be resolved. By using the above-mentioned polyester resin as a raw material for the base layer of the polyester film, it is possible to suppress the generation of foreign matter due to gelation of the polyester resin and aggregation of metal components, thereby increasing the recycle index (R) of the base layer of the polyester film and ultimately building a circular recycling system. By using such polyester resin, it is possible to increase the recycle index while suppressing the deterioration of the polyester film quality, but there is a limit in terms of the deterioration of the polyester resin, so the upper limit of the recycle index (R) of the base layer of the polyester film is 5.0.

[0078] In the recycled raw material for the polyester film of the present invention, when the polyester film has a coating layer or a functional layer on the surface, it is preferable to remove the coating layer from the viewpoint of removing foreign matter. If the recycled raw material with the coating layer remaining is used, various resins, additives, etc. contained in the coating layer are mixed into the polyester base layer, which increases the internal haze and the number of defects inside the film, and when used as an optical film, this can cause quality problems such as an increase in defects in the final product, which is not preferable. That is, the manufacturing method for the polyester film of the present invention is characterized by using a recycled raw material in which the coating layer has been removed from a polyester film provided with a coating layer.

[0079] Methods for removing the coating layer or the functional layer include a method of physically scraping off the surface and a method of dissolving and peeling off with a cleaning agent, but the latter cleaning method using a cleaning agent is preferred from the viewpoint of suppressing the remaining of the coating layer and the like and enabling uniform removal. The cleaning agent used is not particularly limited, but it is preferable to use an alkaline cleaning agent because it acts on the surface of the polyester film and partially decomposes it, thereby enabling efficient removal of the coating layer or the functional layer formed on the film. The alkaline cleaning agent may be either an inorganic alkalizing agent or an organic alkalizing agent, but inorganic alkalizing agents are preferred in terms of removal efficiency.

[0080] Examples of inorganic alkalizing agents include aqueous solutions of alkali metal silicates such as sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, calcium hydroxide, barium hydroxide, etc., sodium carbonate, potassium carbonate, trisodium phosphate, sodium pyrophosphate, sodium tripolyphosphate, sodium tetrapolyphosphate, tripotassium phosphate, potassium pyrophosphate, potassium tripolyphosphate, sodium orthosilicate, sodium metasilicate, and potassium silicate, etc., which may be used alone or in appropriate mixtures. Furthermore, cleaning with these components may be carried out multiple times, and in that case, the type of cleaning agent may be changed appropriately.

[0081] The concentration of the alkaline aqueous solution used in the removal step is preferably pH 10 or more. For example, the concentration of sodium hydroxide is generally 0.1% by mass or more, but is preferably 0.1 to 30% by mass, and more preferably 0.4 to 20% by mass. If the concentration is too low, problems such as insufficient removal of the coating layer or functional layer or excessive removal time may occur. If the concentration is too high, decomposition of the polyester base material may proceed excessively. In addition, the temperature of the alkaline aqueous solution is preferably 50°C or more from the viewpoint of shortening the removal time and improving the removal efficiency, and is more preferably 70°C or more and 100°C or less.

[0082] In order to promote the penetration of the alkalizing agent into the interface between the polyester film and the coating layer / functional layer, alcohols such as methyl alcohol, ethyl alcohol, propyl alcohol, butyl alcohol, benzyl alcohol, ethylene glycol monomethyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol, and diethylene glycol, as well as various surfactants such as nonionic, anionic, and cationic surfactants can be used. As nonionic surfactants, for example, polyethylene glycol ethers, particularly polyethylene glycol ethers of higher alcohols and polyethylene glycol ethers of alkylphenols, are preferably used. Furthermore, a method of increasing hydrophilicity by subjecting the film surface to corona discharge treatment or plasma discharge treatment in advance is also effective in promoting interfacial peeling.

[0083] In order to reduce the amount of the alkalizing agent remaining in the recovered raw material, it is preferable to perform washing with water after washing with an alkaline aqueous solution. If the alkalizing agent remains in the recovered raw material, the amount of foreign matter may increase, deterioration of the polyester resin may be accelerated, and gelled matter may increase. In particular, when sodium hydroxide is used as the alkalizing agent, it is preferable to perform washing with water, since it affects the amount of sodium element remaining in the base layer.

[0084] The polyester film recycling method includes the so-called material recycling method, in which the recovered, crushed and washed film is used as it is, or remelted and pelletized, and the so-called chemical recycling method, in which the film is depolymerized to the monomer or oligomer level and then polycondensed again to regenerate it, but is not particularly limited in the present invention. However, the material recycling method is preferred from the viewpoint of the reduction rate of energy consumption and CO2 generation and the cost of recycling. In the present invention, it is possible to provide a polyester film whose quality is less deteriorated even when the material recycling is repeated. In addition, the recycled raw material may be subjected to solid phase polymerization in order to increase the intrinsic viscosity IV of the polyester resin. EXAMPLES

[0085] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0086] [Measurement methods for physical properties and evaluation of various characteristics] Measurement of physical properties and evaluation of various characteristics were carried out by the following methods.

[0087] (1) Internal haze of polyester film The measurements were performed using a haze meter (HGM-2DP) manufactured by Suga Test Instruments Co., Ltd. A sample of 60 mm x 30 mm was cut out from the polyester film, and the sample was inserted into a quartz cell filled with tetralin and having an optical path length of 1 cm, and the measurement was performed.

[0088] (2) Quantitative determination of germanium, manganese, phosphorus, sodium, and metal elements in the polyester resin composition and polyester film (base layer) (unit: ppm) 5 g of the sample was placed on a platinum dish, melted and carbonized with an electric heater, and then completely incinerated in an electric furnace (700°C) for 1.5 hours. The incinerated material was then dissolved in 5 mL of concentrated hydrochloric acid, and pure water was added to make a 10% hydrochloric acid solution, which was used as the measurement sample. The above solution was used as the measurement sample and quantified using atomic absorption spectrometry (frame: acetylene-air, acetylene-dinitrogen monoxide for germanium element only). The atomic absorption spectrophotometer used was the "ZA-3300" manufactured by Hitachi High-Tech Science Co., Ltd. In addition, in the case of polyester films with a coating layer, the coating layer was removed using the following method before use as the measurement sample.

[0089] In addition, since the film before the coating layer was removed did not contain potassium element, when potassium element was detected in this measurement, it was determined to be derived from residues remaining after functional layer removal, and was therefore excluded from quantification.

[0090] [Removal of coating layer] The polyester film was cut into a 2.0 cm square size, placed in a 7% by mass potassium hydroxide aqueous solution (pH: 14), and washed with stirring for 1 hour at a temperature of 85° C. After washing, the sample was washed twice with pure water for 10 minutes with stirring to obtain a sample from which the coating layer had been removed.

[0091] (3) Intrinsic Viscosity (IV) of Polyester Resin Composition and Polyester Film The polyester resin or polyester film was dissolved in 100 mL of orthochlorophenol (solution concentration C = 1.2 g / mL), and the viscosity of the solution at 25°C was measured using an Ostwald viscometer. The viscosity of the solvent was also measured in the same manner. Using the obtained solution viscosity and solvent viscosity, [η] was calculated according to the following formula, and the obtained value was taken as the intrinsic viscosity (IV). ηsp / C=[η]+K[η] 2 C (Here, ηsp = (solution viscosity / solvent viscosity)-1, and K is the Huggins constant (assumed to be 0.343).)

[0092] (4) Melt resistivity of polyester resin composition and polyester film base layer The polyester resin composition or the pulverized polyester film was vacuum dried at 180°C for 3 hours and then melted at 290°C. An electrode was prepared by sandwiching a "Teflon" (registered trademark) spacer between two copper plates, and this electrode was submerged in the molten resin. A voltage of 5000 V (V) was applied between the electrodes, and the voltage (V') was measured, and the melt resistivity (ρ) was calculated from the following formula. In the case of a polyester film having a coating layer, the coating layer was removed using the method of Reference Example 19 described later, and then the measurement sample was prepared. ρ(Ω cm)=V S R / (I V') In the formula, V is the applied voltage (V), S is the electrode area (cm 2 ), R: resistor resistance (Ω), I: distance between electrodes (cm), V': measured voltage (V).

[0093] (5) Evaluation of foreign matter in polyester resin compositions 0.1 mg of the polyester resin composition was sandwiched between two cover glasses on a hot plate heated to 290°C and melted to prepare a preparation on which a polymer thin film was formed. This preparation was observed under an optical microscope (Olympus Corporation: BX50, 400x, dark field), and all observable light spots were counted. The number of light spots obtained was judged according to the following criteria, with C being a failure. A: 0~5 pieces / 0.1mg B: 6~9 pieces / 0.1mg C: 10 or more / 0.1mg.

[0094] (6) Heat resistance evaluation of polyester resin composition The polyester resin composition was used to prepare three pressed films with a thickness of 100 μm and a width of 5 cm × 5 cm using a press (press: 15-ton, four-column single-acting upward-moving press manufactured by Gonno Hydraulic Machinery Co., Ltd.). After the three pressed films were heat-treated at 230°C for 30 minutes in a hot air dryer, the three pressed films were folded in half while overlapping each other, and the heat resistance was evaluated based on how many films broke. The heat resistance was evaluated according to the following criteria, with C being a failure. A: Not a single sheet of press film was broken. B: One or two sheets of press film were cracked. C: All three press films were cracked.

[0095] (7) Number of internal defects in polyester film One side of the polyester film was filled in with a black oil-based pen (Teranishi Chemical Industry Co., Ltd. Magic Ink No. 500 Black M500-T1) to prepare a sample. From the opposite side to the filled side, a 10 mm wide × 25 mm long range of the sample was observed at 200x magnification (eyepiece 20x, objective lens 10x) using a Keyence laser microscope VK-X100, and the number of foreign objects with a major axis size of 10 μm or more was confirmed. The number of internal defects was evaluated according to the following criteria, with C being a failure. A: The number of foreign objects is 10 / 250 mm 2 The results were as follows. B: 10 foreign objects / 250mm 2Exceeding 30 pieces / 250mm 2 The results were as follows. C: 30 foreign objects / 250mm 2 exceeded.

[0096] [Reference Example 1] Preparation of polyester resin 1 A slurry consisting of 86 parts by mass of terephthalic acid and 37 parts by mass of ethylene glycol (1.15 times the molar amount relative to terephthalic acid) was gradually added to an esterification reactor containing 105 parts by mass of bishydroxyethyl terephthalate (hereinafter referred to as BHT) melted at 250°C, and the esterification reaction was allowed to proceed. The temperature in the reaction system was controlled to be 245 to 250°C, and the esterification reaction was terminated when the reaction rate reached 95%.

[0097] 105 parts by mass (corresponding to 100 parts by mass of PET) of BHT was charged in a molten state from the esterification reactor into the polymerization apparatus, and the temperature was set to 255°C. An ethylene glycol solution of manganese acetate tetrahydrate (23 ppm as manganese element relative to the mass of polyester resin) and germanium dioxide (45 ppm as germanium element relative to the mass of polyester resin) were added. Then, an ethylene glycol solution of phosphoric acid (19 ppm as phosphorus element relative to the mass of polyester resin) and sodium dihydrogen phosphate dihydrate (14 ppm as sodium element and 19 ppm as phosphorus element relative to the mass of polyester resin) was added. Then, an ethylene glycol solution of an equimolar mixture of paratoluenesulfonic acid and tetrabutylphosphonium hydroxide (20 ppm as phosphorus element relative to the mass of polyester resin composition) was added. Note that germanium dioxide was completely dissolved in a 20% by mass aqueous solution of tetraethylammonium hydroxide, and then an ethylene glycol solution to which ethylene glycol was added was used.

[0098] Thereafter, the temperature inside the polymerization apparatus was gradually increased to 290°C, while the pressure was reduced from normal pressure to 133 Pa or less, and the polymerization reaction was allowed to proceed until a predetermined stirring torque was observed at 290°C. After the polymerization reaction was completed, the reaction system was returned to normal pressure with nitrogen gas, and the molten polyester resin composition in the polymerization apparatus was discharged in the form of strands into a water tank and cooled, after which it was cut to obtain a pellet-shaped polyester resin composition, which was designated as polyester resin 1. The properties of the obtained polyester resin are shown in Table 1.

[0099] [Reference examples 2~5, 12~17] Polyester resins 2 to 5 and 12 to 17 were obtained in the same manner as in Reference Example 1, except that the amounts of germanium, manganese, sodium, and phosphorus in the polyester resin were adjusted as shown in Tables 1 and 2. The properties of the obtained polyester resins are shown in Tables 1 and 2.

[0100] [Reference examples 6~8] Polyester resins 6 to 8 were obtained in the same manner as in Reference Example 1, except that an ethylene glycol solution containing an equimolar mixture of paratoluenesulfonic acid and tetrabutylphosphonium hydroxide was not added, and the amount of each component added was changed so that the amount of phosphorus element was as shown in Table 1. The properties of the obtained polyester resins are shown in Table 1.

[0101] [Reference example 9] Polyester resin 9 was obtained in the same manner as in Example 1, except that an ethylene glycol solution of an equimolar mixture of paratoluenesulfonic acid and tetrabutylphosphonium hydroxide was added, and then an ethylene glycol slurry of colloidal silica having an average particle size of 1 μm was added so that the silica content was 0.1 mass% relative to the polyester resin. The properties of the obtained polyester resin are shown in Table 1.

[0102] [Reference examples 10, 11] Polyester resins 10 and 11 were obtained in the same manner as in Reference Example 1, except that an ethylene glycol solution of tetra-n-butoxytitanium (10 ppm as titanium element relative to the mass of the polyester resin composition (Reference Example 10)) or an ethylene glycol slurry of diantimony trioxide (70 ppm as antimony element relative to the mass of the polyester resin composition (Reference Example 11)) was added instead of germanium dioxide. The properties of the obtained polyester resins are shown in Table 2.

[0103] [Reference Example 18] Preparation of water-soluble polyester resin (A) for coating Under a nitrogen gas atmosphere, 88 molar parts of terephthalic acid as a dicarboxylic acid component, 12 molar parts of sodium 5-sulfoisophthalate, and 140 molar parts of ethylene glycol as a glycol component were charged into an ester exchange reactor, and 100 parts by mass of tetrabutyl titanate (catalyst) was added to this in an amount of 1 million parts by mass of the total dicarboxylic acid components. An esterification reaction was carried out at 160 to 240°C for 6 hours, and then the distillate was removed until the reaction product became transparent. Then, a polycondensation reaction was carried out under reduced pressure at 220 to 280°C to obtain a polyester resin composition (A).

[0104] [Reference Example 19] Preparation of recycled raw material The polyester film was crushed to a size of 0.5 cm to 3.0 cm, and then placed in a 5% by mass aqueous solution of sodium hydroxide (pH: 14), and washed at a temperature of 85°C for 1 hour while stirring. After washing, the crushed material was washed with water and dried to obtain a washed crushed polyester film. The crushed material obtained was melted in a two-screw extruder equipped with a vacuum vent, extruded from a nozzle into a strand shape, cooled in a water tank, and cut with a cutter to obtain recycled polyester pellets (raw material). The residual sodium content derived from the aqueous sodium hydroxide solution used in the preparation process of this recovered raw material was 5 ppm by mass relative to the recovered raw material.

[0105] [Reference Example 20] Method for producing polyester film The polyester resin raw material was dried in a vacuum at 160°C for 4 hours, then fed to an extruder and melt-extruded at 285°C. After filtering through a filter with an average aperture of 5μm made by sintering and compressing stainless steel fibers, and then through a filter made by sintering stainless steel powder with an average aperture of 14μm, the sheet was extruded from a T-shaped die, and the sheet was wrapped around a mirror-finished casting drum with a surface temperature of 25°C at a casting speed of 30m / min using an electrostatic casting method, and cooled and solidified to obtain an unstretched film. This unstretched film was preheated to 80°C with a preheating roll, and then stretched 3.1 times in the longitudinal direction by utilizing the difference in peripheral speed between the rolls while heating it to 95°C from above and below using a radiation heater, and then cooled to 25°C with a cooling roll to obtain a uniaxially oriented (uniaxially stretched) film. Next, using a metering wire bar with a wire diameter of 0.1mm (#4), the following aqueous coating solution was measured so that the coating film thickness was 6μm, and this was applied to one surface of the uniaxially stretched film.

[0106] <Coating fluid> An aqueous solution containing the following components and having a concentration of 5.0% calculated as polyester resin solids when the polyester resin solids are 100 parts by mass. Polyester resin (A) obtained in Reference Example 18: 92.5% by mass Melamine-based crosslinking agent ("Nicalac" MW12LF, manufactured by Sanwa Chemical Co., Ltd.): 5% by mass (solid content) Colloidal silica with particle size of 140 nm: 2.5% by mass.

[0107] Both widthwise ends of the uniaxially stretched film coated with the aqueous coating agent were held with clips and transported to an oven, where it was dried and preheated at an atmospheric temperature of 120°C. It was then continuously stretched 3.7 times in the widthwise direction in a 120°C stretching zone. The resulting biaxially oriented (biaxially stretched) film was then heat-treated for 10 seconds in a 230°C heating zone, after which it was cooled from 230°C to 120°C while undergoing a 5% relaxation treatment, and then cooled to 50°C. Both widthwise ends were then removed and the film was taken up to obtain a polyester film with a thickness of 50 μm.

[0108] [Table 1]

[0109] [Table 2]

[0110] [Example 1] (Adjustment of recycled materials) A polyester film was obtained by the method of Reference Example 20 using the polyester resin 1 obtained in Reference Example 1. Next, the coating layer was removed and the obtained polyester film was washed by the method of Reference Example 19 to obtain a recovered polyester raw material (recycle index 2.0).

[0111] (Preparation of polyester film) Using the following polyester resin raw material mixture, a polyester film (recycle index 1.5) was obtained by the method of Reference Example 20. The properties of the obtained polyester film are shown in Table 3. Polyester resin 1 obtained in Reference Example 1: 50% by mass (recycle index 1.0) - Recycled polyester raw material obtained above: 50% by mass (recycle index 2.0).

[0112] [Examples 2 to 17, Comparative Examples 1 to 9] A polyester film was obtained in the same manner as in Example 1, except that the polyester resin raw material used for preparing the recycled raw material and the polyester resin raw material used for preparing the polyester film were as shown in Tables 3 and 4. In Examples 12 and 13 and Comparative Example 9, the recycled raw material was prepared using the films of the respective Examples and Comparative Examples. The properties of the obtained films are shown in Tables 3 to 5. In Comparative Examples 1, 3, 4 to 7, and 9, a large number of translucent foreign matter due to resin deterioration was generated, and in Comparative Examples 2 and 8, in addition to the translucent foreign matter due to resin deterioration, fine aggregates with colored nuclei presumed to be derived from metal were also observed. The polyester film of Comparative Example 10 had low transparency as an optical film and had problems in appearance. In Examples 11 to 13, even when the recycling index was increased, both the foreign matter and transparency did not deteriorate significantly, and good quality was maintained. In Examples 6, 7, 8, and 17, the electrostatic casting property deteriorated, so the cast speed was reduced to 20 m / min to produce the film, but the quality was at an acceptable level.

[0113] [Table 3]

[0114] In the table, the total metal elements in Example 9 is the total value including antimony element derived from polyester resin 11 in addition to those shown in the table.

[0115] [Table 4]

[0116] [Table 5] [Industrial Applicability]

[0117] The polyester film according to the present invention contains little resin thermal degradation products and metal agglomeration foreign matter, and can suppress internal defects, so it can be suitably used as an optical film for displays, which require high quality, etc. Furthermore, even when recycled raw materials made from recycled film are used, defects due to resin degradation and metal agglomeration are unlikely to occur, so it can be suitably used as a high-quality product with reduced environmental impact, which has been in increasing demand in recent years.

Claims

1. A polyester film having a substrate layer mainly composed of a polyester resin, an internal haze of 0.5% or less, and satisfying all of the following formulae (I) to (IV): 5 ppm≦Germanium element content (by mass)≦80 ppm (I) 5 ppm≦Manganese element content (by mass)≦40 ppm (II) 4 ppm≦Sodium element content (by mass)≦40 ppm (III) 14ppm≦Metal element content (mass standard)≦100ppm (IV)

2. The polyester film according to claim 1 , wherein the base layer has a phosphorus element content of 15 ppm to 70 ppm by mass.

3. 3. The polyester film of claim 2, wherein at least a portion of the phosphorus element is derived from phosphoric acid and sodium phosphate.

4. 2. The polyester film according to claim 1, wherein the base layer has a melt resistivity of 10.0 MΩ·cm or less.

5. The polyester film according to claim 1 , further comprising a coating layer on at least one surface of the substrate layer.

6. 10. The polyester film of claim 1, wherein the substrate layer comprises recycled materials.

7. 7. The polyester film of claim 6, wherein the recycled materials comprise self-recycled materials.

8. The polyester film according to claim 6 or 7, wherein the base layer is made of the recycled raw materials and has a recycle index (R) calculated by the following formula (V) of 1.5 or more: [Recycling Index (R)] R=Σ(m n *r n ) (V) n: type of raw material contained in the base layer m n : Mass ratio of each raw material in the recycled base material layer r n :Recycling index of each material defined as follows Non-recycled materials: 1.0 Recovered raw materials: the value obtained by adding 1.0 to the recycling index of the recovered molded body

9. A method for producing the polyester film according to claim 6 or 7, comprising using a recycled raw material obtained by removing a coating layer from a polyester film having a coating layer.

Citation Information

Patent Citations

  • Preparation of aromatic polyester

    JP1988278927A

  • Polyester fiber for reinforcing high toughness rubber

    JP1991146707A

  • Method of producing polyester

    JP2003137992A

  • Polyester recycling system and recycling method

    JP2021160351A

Cited By

  • Polyester resin and polyester film

    JP7885946B1